High energy phosphate transfer by NDPK B/G β γ complexes - an alternative signaling pathway involved in the regulation of basal cAMP production - Hippe, Hans-Jörg; Wieland, Thomas (Journal of bioenergetics and biomembranes, 2006)
The activation of heterotrimeric G proteins induced by G protein coupled receptors (GPCR) is generally believed to occur by a GDP/GTP exchange at the G protein alpha -subunit. Nevertheless, nucleoside diphosphate kinase (NDPK) and the beta-subunit of G proteins (Gbeta) participate in G protein activation by phosphate transfer reactions leading to the formation of GTP from GDP. Recent work elucidated the role of these reactions. Apparently, the NDPK isoform B (NDPK B) forms a complex with Gbetagamma dimers in which NDPK B acts as a histidine kinase phosphorylating Gbeta at His266. Out of this high energetic phosphoamidate bond the phosphate can be transferred specifically onto GDP. The formed GTP binds to the G protein alpha-subunit and thus activates the respective G protein. Evidence is presented, that this process occurs independent of the classical GPCR-induced GTP/GTP exchange und thus contributes, e.g. to the regulation of basal cAMP synthesis in cells.